Information Problems of Practical Training - Kirilov, Rosen (Research Papers, 2019)
The article discusses information, technological and organizational challenges in managing and financing the practical training of students. The main goal is to build on experience and good practices to uncover the information challenges of process efficiency. The tasks are related to the analysis of the characteristics of the processes of conducting and financing of the practical training, consideration of the technological features of the information provision and proposals for conceptual solution of the main information challenges. The results achieved are in the direction of presenting technological and conceptual solutions as well as formulating guidelines for future development.
Keywords: Information technology; Software platforms; Practical training